Re: here a nice problem!!!
- (1+1+1)! = 6<br>2+2+2 = 6<br>3*3-3 =
6<br>sqrt(4)+sqrt(4)+sqrt(4) = 6<br>(5-5)!+5 = 6<br>6+6-6 = 6<br>7-(7-7)! =
6<br>8^(1/3)+8^(1/3)+8^(1/3) = 6<br>sqrt(9)*sqrt(9)-sqrt(9) = 6
- can't sleep (yawn), i spent around 3 hr.s on your your original post here. it seems this implicit function solution set is the semi-stable modular eliptical curves A. Wiles gave in his proof of fermat's last theorem. Your function is way simpler. have to get some sleep before i got to go to work, but the proof of this is around 4 to 5 pages as you said. i'll have to look at it more this evening. also, what's the scoop of you being the source for the plot of tron legacy? we should all get royalties! heheh.
--- In firstname.lastname@example.org, jeshields_98 wrote:
> I hit the wrong button...<br><br>It should be = c^n<br>not + c^n<br><br>very VEEERRRRRYYYYY important<br><br>sorry